Gambaran Keterlibatan Orang Tua Penyintas Covid-19 dalam Mempersiapkan Adaptasi Anak Sekolah Dasar pada Pembelajaran Tatap Muka - Najla Tiara Umah; Rudi Cahyono (Jurnal Syntax Transformation, 2022)
Face-to-face Learning (PTM) for basic education students has its challenges in its implementation, especially the case of the spread of the COVID-19 virus at the level of basic education, which is quite high. The involvement of parents plays a very important role in preparing elementary school children's adaptation to face PTM. This study aims to describe the involvement of parents of COVID-19 survivors in preparing for the adaptation of elementary school children to face-to-face learning by looking at the form of involvement and the factors that influence it. This research uses a qualitative approach with a case study method. The results showed that three research subjects showed involvement at home by providing education about the dangers of the COVID-19 virus by linking previous experiences, paying attention to aspects of family health, and communicating more intensely with children. Involvement in schools is demonstrated by attending parent meetings, providing advice to schools regarding PTM preparation, ensuring school readiness by visiting schools directly, and communicating with schools. The influencing factor is the belief of parents based on the experience of contracting COVID-19, such as excessive worry, understanding of the role of parents, and the belief that they can help children. Another factor is the perception of parents from the surrounding environment, such as from schools in the form of special regulations for the implementation of PTM, the infrastructure supporting health protocols, providing vaccination socialization, and support from teachers and parents of fellow survivors